2019
DOI: 10.2147/ijgm.s198175
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlation of selected stress associated factors with vitamin D deficiency in Jordanian men and women</p>

Abstract: Background: To identify stress associated factors for vitamin D deficiency (VDD) in healthy Jordanian people based on serum 25(OH)D levels. Design: Prospective cohort study. Methods: Three hundred and seventy-one Jordanian men and women aged 17-52 years, who were identified as VD deficient 25(OH)D <30 ng/mL, were eligible to participate in the study. Serum vitamin 25(OH) D was measured using chemiluminescent immunoassay. Cortisol, parathyroid hormone, calcium, phosphate, fasting lipid profile, and blood glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…42 Many studies have positively addressed HCC and cigarette smoking as stress associated factors. 43,44 Accordingly, the variations of stress predictors such as LDL-C and TC were mostly coffee rate consumption dependent, as seen in prior associated studies. 44,45 In this context, our results confirmed the importance of the daily coffee consumption rate on an individual's health as noted in previous studies.…”
Section: Discussionmentioning
confidence: 55%
“…42 Many studies have positively addressed HCC and cigarette smoking as stress associated factors. 43,44 Accordingly, the variations of stress predictors such as LDL-C and TC were mostly coffee rate consumption dependent, as seen in prior associated studies. 44,45 In this context, our results confirmed the importance of the daily coffee consumption rate on an individual's health as noted in previous studies.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, poor quality of sleep in turn might influence 25OHD metabolism, because 25OHD receptors are widely distributed in different regions of the human brain, such as the hypothalamus, prefrontal cortex, central gray, substantia nigra and raphe nuclei, all of which have important roles in sleep regulation [25]. Finally, we cannot exclude a possible interaction between vitamin D and cortisol levels or stress-induced hormonal modifications, since it is very likely that rotating night shift hospital workers may suffer from high level of stress [26].…”
Section: Discussionmentioning
confidence: 97%
“…We also found that stress levels affect vitamin D deficiency in women of childbearing age, consistent with the results of a study by Gwon et al which showed that perceived stress was a risk factor for low 25(OH) D levels in older women [ 12 ]. Abu-Samak et al also reported that there was a weak positive association between vitamin D deficiency and elevated serum cortisol, although it is difficult to determine a direct link between low 25(OH) D levels and stress [ 34 ]. In a similar study, vitamin D levels decreased with the subjective perception of depression [ 15 ], while higher serum 25(OH) D levels showed a higher probability of positive self-perceived mental health [ 16 ]).…”
Section: Discussionmentioning
confidence: 99%